Pengaruh Minat Belajar dan Literasi Digital Terhadap Kompetensi Praktik Manajemen Server Siswa TKJ - Nurul Auliya’il Husna; Yeni Anistyasari; Meini Sondang Sumbawati (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2025)
This study aims to analyze the effect of learning interest and digital literacy on server management practical competence of students in the Computer and Network Engineering (TKJ) program at public and private vocational high schools. The research employed a quantitative approach with an ex post facto design. The population consisted of 120 twelfth-grade TKJ students from one public and one private vocational school in Lamongan Regency, with total sampling used as the sampling technique. Data were collected using Likert-scale questionnaires to measure learning interest and digital literacy, as well as practical tests supported by assessment rubrics to evaluate server management competence. Multiple linear regression analysis was applied after meeting the prerequisite tests. The results revealed that learning interest had a significant effect on server management practical competence, with a t-value of 8.033 and a significance level of 0.000. Digital literacy also showed a significant effect, with a t-value of 4.733 and a significance level of 0.000. Simultaneously, learning interest and digital literacy significantly affected server management practical competence, indicated by an F-value of 45.913 and a significance level of 0.000. The coefficient of determination (R²) was 0.440, indicating that 44% of the variance in server management practical competence was explained by learning interest and digital literacy. These findings suggest that improving students’ server management practical competence requires not only technical skills but also strong learning interest and adequate digital literacy.